Contrast-Induced Encephalopathy Resulting From Use of Ioversol and Iopromide. Issue 1 (January 2020) - Zhang, Guilian; Wang, Heying; Zhao, Lili; Li, Tao; Sun, Man; Zhang, Yiheng; Hu, Hua; Teng, Guoliang; Chen, Jingju; Jian, Yating; Liu, Jiao
Abstract : Background: Contrast-induced encephalopathy (CIE) is a rare disease, whose etiology and risk factors remain unclear and need investigation. Methods: We collected 7 CIE cases from 2646 patients injected with ioversol and 5 CIE cases from 526 patients injected with iopromide, all of whom underwent neurointervention surgery in our regional centers. The incidence of CIE, its characteristics, and risks were analyzed in both groups. Results: The overall incidence of CIE was 0.38%, specifically 0.95% and 0.26% in the iopromide and ioversol groups, respectively; the former incidence was significantly higher than the latter ( P = 0.029). The risk of CIE with iopromide was 3.567 to 3.618 times higher than that with ioversol (single-factor analysis odds ratio [OR], 3.618; 95% confidence interval [CI], 1.144–11.443; P = 0.029; multifactor analysis OR, 3.567 (95% CI, 0.827–15.379); P = 0.088). Moreover, acute cerebral infarction was an independent risk factor for CIE (OR, 4.024; 95% CI, 1.137–14.236; P = 0.031). Contrast-induced encephalopathy could occur within 5 minutes after injecting contrast media. The CIE characteristics differed according to the medium. In the ioversol group, the most common characteristic was visual disorder (71.43%), whereas in the iopromide group, the most common characteristic was delirium (100%). Conclusions: Compared with ioversol, iopromide appeared more likely to lead to CIE. Acute cerebral infarction was an independent risk factor for CIE. The earliest CIE onset was within 5 minutes after injecting contrast. The characteristics of CIE varied significantly for different contrast media.